Correlation of Progranulin, Granulin, Adiponectin and Vaspin with Metaflammation (hs-CRP) in Indonesian Obese Men - Rosalia E Napitupulu; Anna Meiliana; Andi Wijaya (The Prodia Education and Research Institute (PERI), 2013)
BACKGROUND: Obesity is closely related to chronic, low grade systemic inflammation (metaflammation) and it leads to further metabolic complications such as hypertension, atherosclerosis, and type 2 diabetes due to the adipocytokine imbalance. This study was carried out to assess the correlation between progranulin, granulin, adiponectin and visceral adipose tissue-derived serine protease inhibitor (Vaspin) with metaflammation (high sensitivity C-reactive protein (hs-CRP)) in centrally obese men.METHODS: This study was observational with a cross sectional design involving 60 men aged 30-60 years, consisted of 43 obese men (waist circumference (WC) ≥90 cm) and 13 non obese men (WC <90 cm), with no hypertension, and no renal dysfunction. Anthropometric parameters, creatinine, serum glutamic oxaloacetic transferase (SGOT), serum glutamic piruvic transferase (SGPT) and hs-CRP levels were measured. Serum concentrations of progranulin, granulin, adiponectin and Vaspin were measured by ELISA.RESULTS: This study showed in obese men a significant correlation between hs-CRP and Vaspin (r=0.305; p=0.046), non-significant correlation between hs-CRP and progranulin (r=0.048; p=0.758), between hs-CRP and granulin (r=-0.223; p=0.150), also between hs-CRP and adiponectin (r=-0.121; p=0.439). Similar patterns were observed between adipokines level and WC. There were 3 patterns showing increase or decrease of adipokines value with WC between 80-86 cm; subsequently the pattern tended to become flat with WC between 86-105 cm, then showing increase or decrease of adipokines value with WC >105 cm.CONCLUSION: We found metaflammation (hs-CRP) was significantly correlated with Vaspin, but not with progranulin, granulin and adiponectin, in obese men. We suggest the possibility of a dynamic expression of adipokines related to WC that are subjected to adipocytes hypertrophy-hyperplasia phenomenon.KEYWORDS: progranulin, granulin, adiponectin, Vaspin, hs-CRP, metaflammation, central obesity